Pregnant women's contribution in the construction and evaluation of an educational technology: the "Comics for Pregnant Women" - Bruna Carneiro Silva; Cândida Caniçali Primo; Márcia Valéria de Souza Almeida; Ivone Evangelista Cabral; Hugo Cristo Sant'Anna; Eliane de Fátima Almeida Lima
ABSTRACT Objectives: to describe the contribution of pregnant women to the construction and evaluation of educational technology. Methods: a participatory study developed in three stages, which occurred between March 2018 and June 2019 for identifying the content, construction, and evaluation of the comic. Non-directive interviews were conducted in educational groups with 34 pregnant women. After the comic was built by a team, including a designer, an instrument was applied to 41 pregnant women to evaluate the items Objectives, Organization, Writing style, Appearance, and Motivation. Results: the comic contains 40 pages of contents, illustrations, and quizzes (word search, cross-puzzle, seven mistakes, etc). The pregnant women evaluated it as easy to understand, self-explanatory, aesthetically attractive, and capable of motivating good care practices during pregnancy, obtaining a minimum agreement of 92.1%. Final Considerations: the innovation of the educational technology consisted of incorporating the voices of pregnant women in prenatal care, with the potential to stimulate reflections and the learning process of this target audience.